2020
DOI: 10.3390/molecules25071545
|View full text |Cite
|
Sign up to set email alerts
|

Flavones Contents in Extracts from Oroxylum indicum Seeds and Plant Tissue Cultures

Abstract: Oroxylum indicum (L.) Benth. ex Kurz or Pheka, is a plant in the Bignoniaceae family with various traditional uses. The mature fruits promote anti-helminthic and stomachic effects, while the seeds have been used as a purgative and for the relief of tonsil pain. The young fruits are popularly consumed as vegetables, while the seeds are one of the components in traditional drink formulations. To develop new plant raw material sources, a plant tissue culture technique was used to generate plant tissue cultured sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The spectral result of peak 21 showed at m/z 254, which is consistent with the standard chrysin peak [ 13 ]. In the same way, the study of Rojsanga reported that O. indicum seed extract contained 3 major compounds, including baicalein, baicalin, and chrysin [ 14 ]. Thus, a peak 21 could be the chrysin.…”
Section: Resultsmentioning
confidence: 99%
“…The spectral result of peak 21 showed at m/z 254, which is consistent with the standard chrysin peak [ 13 ]. In the same way, the study of Rojsanga reported that O. indicum seed extract contained 3 major compounds, including baicalein, baicalin, and chrysin [ 14 ]. Thus, a peak 21 could be the chrysin.…”
Section: Resultsmentioning
confidence: 99%
“…A decoction of fresh bark offered to animals for deworming has also been demonstrated to be useful when applied to wounds for killing maggots. The plant leaves contain therapeutic agents such as Chrysin (5, 7-dihydroxyflavone) and baicalein (5, 6, 7-trihydroxyflavone) (Rojsanga et al 2020), and have antioxidant, antianaphylaxis and anticancer, anti-diabetes, anti-anxiolytic effect and anti-inflammation properties.…”
Section: Plant Profile and Usesmentioning
confidence: 99%
“…Vasanth et al (1991) extracted Ellagic acid, 8, 8 0 Bis-baicalein, Oroxylin A, and Oroxyloside methylester from the root bark. Ali et al (1998) (Nakahara et al 2001(Nakahara et al , 2002Jiwajinda et al 2002;Chen et al 2003Chen et al , 2005Dinda et al 2007;Yuan et al 2008;Hari Babu et al 2010;Liu et al 2010;Majumdar et al 2010;Yan et al 2011Yan et al , 2014Kruger and Ganzera 2012;Cao et al 2013;Li et al 2014a, b;Das et al 2014;Fan et al 2015;Fuentes et al 2015;Rojsanga et al 2017;Sun et al 2017a;Nagasaka et al 2018;Chetry and Bharali 2018;Sithisarn et al 2019;Hemantha et al 2019;Peng et al 2019;Rojsanga et al 2020).…”
Section: Phytochemistrymentioning
confidence: 99%